Editorial (Intervention. European Journal of Economics and Economic Policies, 2010)
In contrast to the last few issues, this issue's refereed articles are not focused on a specific thematic topic. Two of the six articles take on current questions and developments: Hansjörg Herr analyzes the influence of the financial system on the soaring economic development in China. Thomas Palley shows that central banks have underestimated the emergence of asset bubbles and tries to answer the question of how to avoid this in the future. Three articles are dedicated to the determination, the role or the impact of various macroeconomic factors: consumption (Jan Oliver Menz), income distribution (Guglielmo Forges Davanzati/Andrea Pacella) and uncertainty (Finn Olesen). Finally, Paul Cockshott develops some new thoughts on the historic calculation debate.
Keywords: 330